2022
DOI: 10.1186/s13018-022-03043-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a finite element model and stress analysis of intra-articular impacted fragments in posterior malleolar fractures

Abstract: Background Intra-articular impacted fragments (IAIFs) are considered articular surface fragments resulting from impact and compressive forces. The malreduction of IAIFs in posterior malleolar fractures has been associated with talar subluxation and long-term post-traumatic arthritis. In this study, we establish IAIF defect finite element models of different sizes in posterior malleolar fractures and explored how IAIF defects predict the onset of post-traumatic arthritis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Based on these research findings, Xie utilized finite element analysis in conjunction with linear equations to estimate that a joint surface defect greater than 17.2 mm 2 would result in the maximum contact stress on the joint surface exceeding 4.5 MPa. It was also emphasized that as the defect size increases, so does the corresponding increase in maximum contact stress on the joint surface, underscoring its significance in clinical treatment [10].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on these research findings, Xie utilized finite element analysis in conjunction with linear equations to estimate that a joint surface defect greater than 17.2 mm 2 would result in the maximum contact stress on the joint surface exceeding 4.5 MPa. It was also emphasized that as the defect size increases, so does the corresponding increase in maximum contact stress on the joint surface, underscoring its significance in clinical treatment [10].…”
Section: Resultsmentioning
confidence: 98%
“…IAIF is associated with prognosis of posterior malleolar fracture [6,9]. Xie et al concluded that when the defect of IAIF in the posterolateral area of the distal tibial articular surface was larger than 17.2mm 2 , patients are more likely to develop post-traumatic osteoarthritis [10].…”
Section: Introductionmentioning
confidence: 99%